Meningkatkan Kemampuan Bernalar Kritis Dalam Metode Project-Based Learning (PBL) melalui Media Komik Digital pada Materi Konsekuensi Pewartaan Yesus Fase D Kelas VIII SMP Negeri 1 Siding - Margayanti F; Timotius Tote Jelahu; Modestus Haryono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aimed to improve the learning outcomes of Grade VIII students at SMP Negeri 1 Siding in the 2024/2025 academic year in the subject of Catholic Religious Education and Character through the implementation of the Problem Based Learning (PBL) model with digital comic media. This study is a Classroom Action Research (CAR) conducted over two cycles. Each cycle consisted of several stages: planning, action, observation, and reflection. The first and second cycles covered the topics of the Passion, death, and Resurrection of Jesus. The subjects of this study were 17 Catholic students in Grade VIII at SMP Negeri 1 Siding for the 2024/2025 academic year. Data collection techniques were carried out through tests and observations, with supporting techniques including documentation. The results showed that the application of the Problem Based Learning (PBL) model with digital comic media could improve students' critical reasoning skills, as evidenced by the comparison between the first and second cycles. Based on observational data, the average critical reasoning ability of students in the first cycle was 76, which increased to 83 in the second cycle, with an average improvement of 8.64%. This indicates that the Problem Based Learning method with digital comic media can enhance critical reasoning skills in the subject of the Consequences of Jesus' Proclamation for Phase D, Grade VIII at SMP Negeri 1 Siding.